A genomic audit of newly-adopted autosomal STRs for forensic identification. (July 2017) - Phillips, C.
Highlights: Recently new capillary electrophoresis kits and massively parallel sequencing kits incorporated 41 supplementary STRs new to forensic use. These STRs were audited for genomic status and linkage to core STRs, 35 had global population data and forensic informativeness metrics compiled. Sequence characteristics, repeat structures and flanking regions of each STR were compiled from the current human reference sequence. A further 44 novel autosomal STRs not in commercial kits but of interest had sequence details compiled in slightly less detail. Abstract: In preparation for the growing use of massively parallel sequencing (MPS) technology to genotype forensic STRs, a comprehensive genomic audit of 73 STRs was made in 2016 [Parson et al., Forensic Sci. Int. Genet. 22, 54–63]. The loci examined included miniSTRs that were not in widespread use, but had been incorporated into MPS kits or were under consideration for this purpose. The current study expands the genomic analysis of autosomal STRs that are not commonly used, to include the full set of developed miniSTRs and an additional 24 STRs, most of which have been recently included in several supplementary forensic multiplex kits for capillary electrophoresis. The genomic audit of these 47 newly-adopted STRs examined the linkage status of new loci on the same chromosome as established forensic STRs; analyzed world-wide population variation of the newly-adopted STRs using published data; assessed their forensic informativeness; and compiled the sequence characteristics, repeat structures and flanking regions of each STR. A further 44 autosomal STRs developed for forensic analyses but not incorporated into commercial kits, are also briefly described.